Perlindungan Hukum Terhadap Pembeli Barang Hasil Lelang Eksekusi (Studi Pada Kantor Pelayanan Kekayaan Negara Dan Lelang (KPKNL)) Cabang Sumatera Utara - Emmi Rahmiwita Nasution (Citra Justicia : Majalah Hukum dan Dinamika Masyarakat, 2021)
Abstract ln setling out to public by auction is a matter that hos been ruled and for it is fted particularly as contained on the Auction Regulations made by Dutch ruler namely fu Reglentent, Staatsbfad No. 189 of 19A8 ond got amendment to Staatbtad of 1941 No.3 to adopt it througlt now an effective still with other regul.atians. ln administering an , tegal protection fcr buyer in auction with exeeulion espeeially to one with good ,r is highly required particutarly for realizing justice, effectiveness and legat certiinty ta the existence of law purpase. This study is infended ta knaw how the legat tion to the buyer of auctian executed and whether the regulations ovailable is in t to generate the protectian or require yet more explonctfon for legal certainty buyer in auction axecution. : {ego{ protec{,ian, buyer in auction with execution, KpKNL.